2018
DOI: 10.3389/fphys.2018.01701
|View full text |Cite
|
Sign up to set email alerts
|

Interlimb Asymmetries Identified Using the Rate of Torque Development in Ballistic Contraction Targeting Submaximal Torques

Abstract: Evaluating the rate of torque development (RTD) in isometric ballistic contraction targeting submaximal torques is usually overlooked in the literature. In a series of isometric ballistic contractions targeting a range of submaximal torque values, there is a linear relationship between the peak torque and the peak RTD obtained in each contraction. RTD scaling factor (RTD-SF) represents the slope of this relationship. In this study, we investigated the prevalence of interlimb asymmetry in the RTD-SF and in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 45 publications
1
22
1
Order By: Relevance
“…The use of the rate force development scaling factor (RFD-SF) to assess rapid force generation has been more frequently performed and reported after the protocol verification by Bellumori et al (2011) . Since then RFD-SF protocol has been used for isometric neuromuscular assessment of different muscle groups ( Casartelli et al, 2014 ; Djordjevic and Uygur, 2017 ), to explore the effects of aging ( Bellumori et al, 2013 ) and different diseases such as osteoarthritis ( Šarabon et al, 2020a ), and in studies exploring lateral asymmetries in different sports ( Boccia et al, 2018 ; Smajla et al, 2020 ). Moreover, some studies have shown that rate of force relaxation scaling factor (RFR-SF) can be assessed using the RFD-SF protocol with the aim to evaluate the ability of quick relaxation of submaximal muscle forces ( Mathern et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of the rate force development scaling factor (RFD-SF) to assess rapid force generation has been more frequently performed and reported after the protocol verification by Bellumori et al (2011) . Since then RFD-SF protocol has been used for isometric neuromuscular assessment of different muscle groups ( Casartelli et al, 2014 ; Djordjevic and Uygur, 2017 ), to explore the effects of aging ( Bellumori et al, 2013 ) and different diseases such as osteoarthritis ( Šarabon et al, 2020a ), and in studies exploring lateral asymmetries in different sports ( Boccia et al, 2018 ; Smajla et al, 2020 ). Moreover, some studies have shown that rate of force relaxation scaling factor (RFR-SF) can be assessed using the RFD-SF protocol with the aim to evaluate the ability of quick relaxation of submaximal muscle forces ( Mathern et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our high r 2 values in both legs and muscle groups indicate that the time to reach peak torque does not variate, regardless of torque amplitude [19]. Potential differences in RTD-SF ability between legs have been investigated in only one study [5] for knee joint. They revealed 17.7% (knee flexors) and 17.4% (KE) of asymmetric young football players which is consistent with our results.…”
Section: Discussionmentioning
confidence: 88%
“…put high demands on rapid force/power production and control. RTD-SF could be useful method for identifying interlimb asymmetries as it was revealed that identifies more subjects with KE asymmetry (17.4%) compared to RTD (8.5%), maximal force (9.9%) and isokinetic (6%) [5]. As we already mentioned, RTD-SF protocol assesses neuromuscular ability to produce explosive joint torques over a wide range of submaximal intensities (not only maximal intensity).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To evaluate inter-limb differences for rapid force production during different submaximal exercises, the rate of force development scaling factor (RFD-SF) was proposed as a measure with higher ecological validity than the RFD (Boccia et al, 2018). In the RFD-SF protocol, the participant needs to perform rapid isometric contractions corresponding to different submaximal percentages of the previously assessed maximal force during MVC.…”
Section: Introductionmentioning
confidence: 99%